Paclitaxel prodrug based mixed micelles for tumor-targeted chemotherapy - Tang, Dongyang; Zhao, Xin; Yang, Tie; Wang, Cheng (RSC advances, 2018)
An effective chemotherapy is usually subject to an insufficient loading of hydrophobic drugs as well as severe side effects. In order to address these dilemmas in one formulation, we herein construct paclitaxel prodrug based mixed micelles (MMs) for tumor-targeted chemotherapy. The paclitaxel prodrug containing a hydrophobic PTX and a hydrophilic PEG chain can self-assemble into uniform MMs with distearoyl phosphoethanolamine-polyethylene glycol-folate (DSPE-PEG-FA). The resultant MMs with preferable stability and hemolysis compatibility could improve the cellular uptake of nanoparticles via FA receptor-mediated endocytosis as compared to the single micelles (SMs). This tumor targetability was also confirmed in vivo by fluorescent imaging. MMs with a stable drug loading as well as tumor targetability displayed elevated in vitro cytotoxicity and in vivo antitumor efficacy compared with Taxol, which could be a potential formulation for cancer therapy. Paclitaxel prodrug based mixed micelles with high drug loading and tumor targeting capacity for elevated chemotherapy.